Morpho-anatomical responses of Catharanthus roseus due to combined heavy metal stress observed under Scanning Electron Microscope - Soumya, V; Kiranmayi, P; Siva Kumar, K (Plant Science Today, 2022)
Heavy metals trigger various plant responses that basically vary with the intensity as well as duration of stress. Comprehension of the morphological and anatomical responses to such stress is essential for a holistic perception of plant resistance mechanisms to metal-excess conditions in higher plants. In the present study, the effects of heavy metals on morpho-anatomy of Catharanthus roseus based on its potential to tolerate metal stress has been studied in industrially polluted environments. The tissue samples of these plants grown in contaminated and uncontaminated soils were processed for analysis under Scanning Electron Microscope (SEM). Briefly, harvested tissues were pre-fixed using glutaraldehyde and paraformaldehyde in sodium cacodylate (CAC) buffer, followed by post fixation in osmium tetroxide. Further, the digital micrographs of critically dried samples were captured. The analysis of micrographs revealed structural changes like cell wall thickening, increased stele diameter, increased root and shoot diameter, variations in stomatal number, enlargement of trichomes and salt glands of plants grown in contaminated soil when compared to those grown in uncontaminated soil. The study also provided microscopic evidence of endophytic colonization of microorganisms within surface-disinfected plant tissues. Based on the varied morpho-anatomical responses due to heavy metal stress, several physiological and metabolic mechanisms of plants were deciphered.